A postwar history of the rules vs discretion debate - V. ARGY (PSL Quarterly Review, 2013)
The work reviews the post-war history of the rules vs discretion debate. The focus is principally on theoretical developments which came to have a bearing on the debate. With the central figure of the debate being, without a doubt, M. Friedman, much of the huge literature centres around arguments first raised by him. Hence, special attention is paid to his contributions.